Herbidospora soli sp. Nov., isolated from soil - Niemhom, Nantawan; Thawai, Chitti (My University, 2018)
A novel actinomycete strain PS42-9T, which formed short chains of spores borne on the tip of long sporophores arising from the substrate mycelium, was isolated from soil in Phu-Sang National Park, Phayao province, Thailand. The isolate contained meso-diaminopimelic acid in the cell-wall peptidoglycan. The whole-cell sugars of strain PS42-9T were glucose, madurose, mannose, rhamnose and ribose. The characteristic phospholipids were phosphatidylethanolamine, phosphatidylmethylethanolamine, hydroxyphosphatidylethanolamine and ninhydrin-positive glycophospholipids. The major menaquinone was MK-10(H4). The main cellular fatty acids were C17:1ω8c and C17: 0. The G+C content of the genomic DNA was 71.5 mol%. Phylogenetic analysis using 16S rRNA gene sequences revealed that strain PS42-9T should be classified in the genus Herbidospora and was closely related to Herbidospora sakaeratensis DMKUA 205T (99.10 %) and Herbidospora yilanensis NBRC 106371T (98.61 %). The result of DNA–DNA hybridization and some physiological and biochemical properties indicated that strain PS42-9T could be readily distinguished from its closest phylogenetic relatives. On the basis of these phenotypic and genotypic data, this strain represents a novel species, for which the name Herbidospora soli sp. nov. is proposed. The type strain is PS42-9T (=BCC 46909T=NBRC 108780T).
Keywords: 16S rRNA gene; Actinomycetes; Herbidospora soli sp. nov